Novel Anti-Tubulin Compounds from Trigonella foenum-graecum Seeds; Insights into In-vitro and Molecular Docking Studies - Alghamdi SS; Suliman RS; Alsaeed AS; Almutairi KK; Aljammaz NA; Altolayyan A; Ali R; Alhallaj A (Dove Medical Press, 2021)
Sahar Saleh Alghamdi,1,2 Rasha Saad Suliman,1,2 Amjad Sulaiman Alsaeed,1 Khlood Khaled Almutairi,1 Norah Abdulaziz Aljammaz,1 Abdulelah Altolayyan,2 Rizwan Ali,2 Alshaimaa Alhallaj2 1College of Pharmacy, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi Arabia; 2Medical Research Core Facility and Platforms, King Abdullah International Medical Research Center (KAIMRC), Ministry of National Guard Health Affairs, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Sahar Saleh Alghamdi Tel +966 114299999 ext 99516Email ghamdisa@ksau-hs.edu.saBackground: Fenugreek, also known as Trigonella foenum-graecum L, is a natural plant that belongs to the Fabaceae family and has been known as a promising source of bioactive compounds. It has been widely used as traditional medicine since it has shown to lower blood glucose, manage cholesterol levels and further aid in the prevention and treatment of cancer. Herein, we aim to evaluate the anticancer activity of methanolic fenugreek seed extract against several cancer cell lines.Methods: We sought to investigate the phytochemical classes present in multiple fenugreek seeds extracts using HPLC-DAD followed by LC/MS, predict and investigate anticancer activity using PASS online webserver, the CellTiter-Glo assay, evaluate ADME properties, and perform molecular docking for all bioactive compounds via Maestro software.Results: Multiple extracts exhibited distinct phytochemical classes that demonstrated different biological activities. Fenugreek methanolic extract contains flavonoid chemical class, which showed the highest anticancer activity against the HCT8 cell line of colorectal cancer (IC50 of 8.83 μg/mL), followed by KAIMRC1 breast cancer cell line (IC50 of 35.06 μg/mL), HL60 leukemia cell line (37.80 μg/mL), MDA-MB-231 breast cancer cell line (38.51 μg/mL), and lastly, HCT116 colorectal cancer cell line with IC50 of 56.03 μg/mL. In contrast, the chloroform extract was inactive. The molecular docking study for all the bioactive compounds suggested that flavonoids F6 (− 9.713 and − 12.132), F7 (− 10.166 and − 12.411), and F11 (− 10.084 and − 13.516) possess the highest docking scores through SP and XP scores, respectively.Conclusion: The obtained results confirm that the bioactive compounds present in fenugreek seeds exhibit anticancer activity against several cancer cells that can mediate via tubulin polymerization inhibition. Although our study has evaluated the anticancer potential of Trigonella foenum-graecum as a promising natural source for new anticancer agents, fenugreek biological activity needs further research and investigations on their mechanism of action and toxicity profile.Keywords: fenugreek Trigonella foenum-graecum, tubulin inhibitors, computational pharmacokinetics ADME, QTOF-LC/Ms metabolites